2010
DOI: 10.1143/jjap.49.087002
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Relaxation Analysis of Single-Stranded DNA in Liquid Crystals

Abstract: Since liquid crystals have found wide use in liquid crystal displays, we try to apply liquid crystals to biotechnology. The purpose of this study is to describe the physical properties of the biopolymer DNA in regard to electrooptics. Synthetic oligonucleotide molecules were dispersed in a nematic liquid crystal (NLC). The ICP analyses showed that all of the oligonuleotide molecules added dispersed in the NLC. This sample was injected into the twisted nematic liquid crystal display cells, and then we measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…During a series of measurements, some interesting results have emerged and these will be discussed in relation to their biological applications. First, we measured the dielectric properties of NLCs doped with ssDNA (A10b, C10b, G10b, and T10b) [ 53 ]. The result shows that 5CB doped with oligonucleotide exhibits dielectric relaxation from 10 1 to 10 2 Hz, as shown in Figure 5 .…”
Section: Biological Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…During a series of measurements, some interesting results have emerged and these will be discussed in relation to their biological applications. First, we measured the dielectric properties of NLCs doped with ssDNA (A10b, C10b, G10b, and T10b) [ 53 ]. The result shows that 5CB doped with oligonucleotide exhibits dielectric relaxation from 10 1 to 10 2 Hz, as shown in Figure 5 .…”
Section: Biological Applicationsmentioning
confidence: 99%
“…( A ) shows the real part of the dielectric permittivity ε’ and ( B ) shows the imaginary part of the dielectric permittivity ε”. Adapted with permission from [ 53 ]. Copyright 2010 The Japan Society of Applied Physics.…”
Section: Biological Applicationsmentioning
confidence: 99%
“…We found a difference in electrical conductivity between the Watson-Crick base pairs (AT and GC). 1) This difference might have originated from the existence of a functional group involved in a hydrogenbond interaction. 1) In the present study, we have determined the characteristics of the frequency modulation (FM) response in twist nematic liquid crystal displays (TN-LCDs) doped with G10b, where 5CB NLC was also used as the host medium.…”
mentioning
confidence: 99%
“…1) This difference might have originated from the existence of a functional group involved in a hydrogenbond interaction. 1) In the present study, we have determined the characteristics of the frequency modulation (FM) response in twist nematic liquid crystal displays (TN-LCDs) doped with G10b, where 5CB NLC was also used as the host medium. We found that the frequency range of the FM effect extends from several tens of Hz to an upper limit of 100 Hz.…”
mentioning
confidence: 99%
See 1 more Smart Citation